A token of love : [large type] a novel - Turansky, Carrie (Center Point Large Print, 2024)
"Separated by centuries, the lives of two women intertwine through their shared pursuit of love, truth, and justice. In 1885 London, Lillian Freemont embarks on a treacherous journey to reunite with her long-lost niece, Alice, who was abandoned at the Foundling Hospital eight years ago. Fueled by her sister's plea and armed with the gold token that identifies her niece, Lillian teams up with investigative reporter Matthew McGivern to expose the grim reality of the shadowed streets of London. As Lillian and Matthew unravel the mystery of Alice's disappearance, their partnership blossoms into one of shared purpose and undeniable attraction. In present-day London, Janelle Spencer finds herself unexpectedly running the Foundling Museum. When filmmaker Jonas Conrad arrives to document the museum's history, their collaboration takes a surprising turn as they uncover articles from the past that shed light on a haunting connection to the present. As Janelle becomes caught between exposing the truth and protecting the museum's reputation, she must decide if she can risk everything for what she believes."--